2021
DOI: 10.3390/su14010032
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Financial Literacy, Practicality, and Consumer Lifestyle on the Use of Chip-Based Electronic Money Using SEM

Abstract: Industry 4.0 trends have a significant influence on the acceleration of technology in Indonesia. The development of financial technology has shifted conventional transactions to electronic money as a means of payment with a digital system. Electronic money users in Indonesia continue to grow, while several factors affect consumer decision making to use electronic money. This study aims to analyze the effect of financial literacy, practicality, and consumer lifestyle on consumer interest in using chip-based ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…These results confirm H1. These results are consistent with those of previous studies (Hilgert et al 2003 ; Christelis et al 2010 ; van Rooij et al 2011 ; Morgan and Long 2019 ; Foster and Johansyah 2021 ; Morgan and Long 2018 ). However, our findings differ from Li et al’s ( 2020 ) and Chen and Xiang’s ( 2021 ) findings.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
See 2 more Smart Citations
“…These results confirm H1. These results are consistent with those of previous studies (Hilgert et al 2003 ; Christelis et al 2010 ; van Rooij et al 2011 ; Morgan and Long 2019 ; Foster and Johansyah 2021 ; Morgan and Long 2018 ). However, our findings differ from Li et al’s ( 2020 ) and Chen and Xiang’s ( 2021 ) findings.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 93%
“…Individuals with higher financial literacy are more likely to avoid such risks because they have a higher propensity to choose suitable financial products (Agarwal et al 2020 ; Gathergood and Weber 2017 ), detect risky services (Engels et al 2020 ), and detect fraud (Wei et al 2021 ). Several studies have examined the effects of financial literacy on the adoption of fintech services, including ePayment services (Li et al 2020 ; Morgan and Long 2018 ; Foster and Johansyah 2021 ; Lo Prete 2022 ), mobile money, digital banking (Yates 2020 ; Frimpong et al 2022 ; Chen and Xiang 2021 ), peer-to-peer (P2P) lending (Gonzalez 2022 ), or holding cryptocurrencies (Fujiki 2020 ). While some studies argue that individuals with higher financial literacy might recognize the risks they may incur when using fintech services, they are less likely to adopt fintech services (Li et al 2020 ; Chen and Xiang 2021 ).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies in the area of FinTech acceptance and information systems have found that FL affects acceptance and adoption behavior [31,39,59,60]. However, limited research efforts have investigated whether FL could have a moderating role in the UTAUT model, e.g., [41].…”
Section: Financial Literacy (Fl)mentioning
confidence: 99%
“…South Asian countries are “leapfrogging” from the traditional to the digitalized financial world (Lyons et al , 2020); for a smooth transition, it is imperative to first ensure that users have adequate digital financial literacy, as it plays a significant role in FinTech adoption (Jünger and Mietzner, 2020). Previous studies have reported that financial literacy is a determinant of users’ technology adoption intention and acceptance behavior (Setiawan et al , 2021; Foster and Johansyah, 2022).…”
Section: Research Model Development and Hypotheses Formulationmentioning
confidence: 99%